IDDF2022-ABS-0103 A selective class I HDAC inhibitor recovers intratumoral interferon signaling to overcome immune-checkpoint blockade resistance in hepatocellular carcinoma. (2nd September 2022) - Tu, Yalin; Xiong, Zhewen; Zhong, Chengpeng; Wu, Haoran; Wang, Jing; Wong, Patrick Pak-Chun; Yang, Weiqin; Zhou, Jingying; To, Ka-Fai; Sung, Joseph; Chan, Stephen Lam; Kerr, David; et al.
Abstract : Background: Immune checkpoint blockade (ICB) therapies by antibodies have revolutionized the treatment paradigm for a variety of cancers. Although subsets of people exhibit durable responses, resistance and relapse are common in hepatocellular carcinoma (HCC). Methods: ICB-resistant orthotopic-grafted murine models were established via a serial selection of HCC cells in ICB-treated mice. Single-cell RNA-seq and single-cell multiomics, which enable simultaneous profiling of the transcriptome and chromatin landscape in the same single nuclei, were applied to decode the mechanisms underlying the ICB resistance and the epigenetic re-sensitization of ICB therapy, respectively. Multicolor flow cytometry was used to determine the immune profiles. Results: We successfully established the ICB-resistant murine models of HCC, and clarified their cellular and molecular reprogramming during the ICB therapy. Notably, our single-cell transcriptome analysis revealed that tumor intrinsic interferon-gamma (IFNγ) response was most significantly suppressed in ICB-resistant tumors, which was associated with decreased T cell activation and intratumoral infiltration. More importantly, we found that a novel specific class I histone deacetylase (HDAC) inhibitor CXD101 synergised with PD-(L)1 antibody to eradicate the tumor and prolong survival in our ICB-resistant mouse models, which was accompanied by enhanced intratumoral infiltration and activation of cytotoxic lymphocytes. Mechanistically, CXD101 combined with PD-L1 inhibition dramatically recovered the silenced tumor IFNγ pathway via enhancing the chromatin accessibility of key IFNγ responsive genes, thereby triggering an antitumor immune response. Conclusions: Our findings suggest that the corruption of tumor intrinsic IFNγ response may confer ICB resistance during the cancer cell evolution upon ICB therapy, which can be rectified by selective class I HDAC inhibition.